Language Attitudes and Application in the movie The Amazing Spiderman: Sociolinguistics Studies - Edwin Pradinata Samuel; Ervina CM. Simatupang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study are to analyze the types of language attitudes occurs in the movie Amazing Spiderman and the type of meaning from the source taken from the official movie script. The method is used in this study is descriptive analysis method. By using Perloff, (2003) theory the researcher found that there are two types of language attitudes occurs in the movie which are attitudes to Vernacular and attitude to standard English. Vernacular is using a language or dialect native to a region or country rather than a literary, cultured, or foreign language  of relating or being a nonstandard language or dialect of a place, region, or country. Standard English is the English used by educated people with relatively high social status. Moreover,  Attitudes to language are important to sociolinguistic for a study of reasons.